Trademark Counterfeiting of Watches of Famous Brands MUI Fatwa Perspective No. 1/5/2005 and Law No. 20 2016 on Trademarks and Geographical Indications - Erniawati; Annisa Sativa (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
Trade competition has intensified the competitiveness among various trademarks, particularly well-known trademarks, including those used in the watch industry. However, this condition has also increased the circulation of counterfeit watches, causing significant losses to trademark owners and consumers. This study aims to identify the indicators of trademark counterfeiting in the trade of well-known branded watches, analyze trademark counterfeiting from the perspective of Law No. 20 of 2016 on Trademarks and Geographical Indications, and examine such practices from the perspective of Fatwa of the Indonesian Council of Ulama (MUI) No. 1/MUNAS VII/MUI/5/2005 on the Protection of Intellectual Property Rights. This research employs a normative juridical method using the statutory approach and the conceptual approach. Data were collected through document analysis and examined qualitatively. The findings indicate that trademark counterfeiting constitutes a violation that may cause substantial losses to legitimate companies as the original owners and producers of the trademarks. Trademark counterfeiting is an unlawful act prohibited under both Indonesian positive law and Islamic law. According to MUI Fatwa No. 1/MUNAS VII/MUI/5/2005 on the Protection of Intellectual Property Rights, the trade of counterfeit branded watches is considered haram because it constitutes an act of injustice (ẓulm). Furthermore, under Law No. 20 of 2016, any party who permits or facilitates trademark infringement acts contrary to the objective of legal protection for trademarks. Therefore, both the MUI Fatwa and the Trademark Law prohibit trademark counterfeiting, including for parties who knowingly obtain financial benefits from transactions involving counterfeit branded goods.